PENYULUHAN UNTUK MENCEGAH KECACINGAN PADA ANAK SDN 208/IV TELANAI PURA GUNA MENINGKATKAN KONSENTRASI BELAJAR PADA ANAK - Hanina Hanina; Rita Halim; Putri Sari Wulandari; Maria Estela Karolina (Universitas Jambi, 2023)
ABSTRACTThe prevalence of worm infection in children in Indonesia is still quite high, that is approximately 45-65% and in areas with poor environmental conditions it can reach 80%. Worm infection result in loss of nutritional intake such as carbohydrates and protein which has an impact on reducing the quality of resourcesman. This condition can hinder physique development, intelligence and productivity, lower body resilience, decrease human resources and increase risk of ill and death. Prevention and control of worm infection requires effort to increasing clean and healthy living behavior. SDN 208/IV is one of the public elementary schools in Jambi City which was founded in 2017 and is still accredited C. This elementary school still lacks facilities, including cleaning facilities or toilets. This can be a health problem because PHBS certainly requires adequate facilities. The education program were carried out targeting all students at SDN 208/IV Jambi City using an interactive discussion method. This program aims to increase children's knowledge about worms that can infect humans, symptoms, transmission methods, prevention and treatment of worm infections. Beside that, a six-step hand washing exercise demonstration was also carried out so that children could apply PHBS well. Level knowledge respondents be measured throughquestionnaire as much two time that is before counseling (pre test) and after counseling (post test) whichconsists from 20 item question. From data analysis of questionnaire results before counseling (pre test) andafter counseling (post test) obtained average (mean) results pre test 70.12 with a standard deviation of 13.78 and an average post test result of 80.56 with a standard deviation of 1 1.40 . There was increase in average yield questionnaire after counseling compared before counseling. It means counseling to students at SDN 208/IV Jambi City enough beneficial in increase knowledge student about prevention worms.Keywords: worms, counseling, SDN 208/IV ABSTRAKPrevalensi kecacingan pada anak di Indonesia masih cukup tinggi yaitu antara 45-65% dan di daerah yang kondisi lingkungannya buruk bisa mencapai 80%. Kecacingan mengakibatkan kehilangan asupan gizi seperti karbohidrat danprotein serta kehilangan darah yang berdampak menurunnya kualitas sumber dayamanusia. Kondisi ini dapat menghambat perkembangan fisik, kecerdasan dan produktivitas, menurunkanketahanan tubuh sehingga mudah terkena penyakit sehingga berakibat menurunnya kualitas sumberdaya manusia dan risiko tinggi kesakitan dan kematian. Pencegahan dan penanggulangan penyakit kecacingan memerlukan upaya peningkatan perilaku hidup bersih dan sehat (PHBS). Pada kegiatan pengabdian ini, dilakukan penyuluhan dengan metode diskusi interaktif untuk meningkatkan pengetahuan anak mengenai cacing yang dapat menginfeksi manusia, gejala, cara penularan, pencegahan dan pengobatan infeksi cacing. Selain itu juga dilakukan demonstrasi senam cuci tangan enam Langkah agar anak dapat menerapkan PHBS dengan baik. Tingkat pengetahuan responden diukur melalui kueisionersebanyak dua kali yaitu sebelum penyuluhan (pre test) dan setelah penyuluhan (post test) yang terdiri dari20 butir pertanyaan. Dari analisis data hasil kueisioner sebelum dilakukan penyuluhan (pre test) dansesudah dilakukan penyuluhan (post test) diperoleh rata-rata (mean) hasil pre test 70,12 dengan standar deviasi 13,78 dan rata-rata hasil post test 80,56 dengan standar deviasi 11,40. Dapat disimpulkan bahwa terdapat peningkatan rata-rata hasil kueisioner sesudah penyuluhan dibanding sebelum penyuluhan. Hal ini berarti penyuluhan terhadap siswa di SD N 208/IV Kota Jambi ini cukup bermanfaat dalam meningkatkan pengetahuan siswa mengenai pencegahan cacingan.Kata kunci: kecacingan, penyuluhan, SDN 208/IV Â